Analisis Peluang Usaha Baru dan Studi Kelayakan Usaha BUMDesa Medalsari - Roby Syaiful Ubed; Taufik Raharjo; Ambang Aries Yudanto; Mulyadi Mulyadi (Journal Pemberdayaan Masyarakat Indonesia, 2025)
This community service program aims to compile a feasibility study of the business that will be run by BUMDesa Medalsari. Based on the implementation of activities in Medalsari Village related to the preparation of the feasibility study of the BUMDesa business plan, it can be concluded that this program has been running well and has produced output by the set targets. The entire series of activities were carried out in stages through Focus Group Discussions (FGD), field observations, and mentoring. FGD activities resulted in mapping problems and determining priorities for their resolution. Through observation, information was obtained regarding the geographical conditions, potential, and challenges in Medalsari Village. Meanwhile, mentoring activities produced a book containing the potential and business opportunities for BUMDesa Medalsari.